THE TRANSBOUNDARY WATER MANAGEMENT – COMPARING POLICY TRANSLATIONS OF THE WATER FRAMEWORK DIRECTIVE IN THE INTERNATIONAL BASIN DISTRICTS OF THE ODER RIVER AND THE TORNE RIVER - Ibragimow, Aleksandra; Albrecht, Eerika; Albrecht, Moritz (Quaestiones Geographicae, 2019)
The European Union’s Water Framework Directive introduced a new approach to the system of water management in Europe by nominating the river basin district as the basic unit in water management. While its transboundary character aims to better manage natural resources, its design and implementation carries several challenges due to its weak integration of various bordering effects related to administrative boundaries that strongly affect the directives’ implementation. Based on a comparative document based case study of two river basin districts – the International Oder River Basin District (IORBD) and the International Torne River Basin District (ITRBD) – the paper scrutinizes the effects on the implementation processes of the directive and aims to draw attention to identify the differences that derive from various socio-spatial settings during the first cycles of water management plans from 2009 to 2015. By thematically comparing biophysical characteristics, cross-border cooperation, cultural and administrative bordering processes the study displays a mismatch between the directives aims for transboundary governance and the actual governance processes which are hampered by a variety of conflicting bordering processes.